Customary Criminality, Bride Abduction, and the Limits of Living Law: A Comparison of Article 25 of Makassaarsche Chrestomathie in Global Perspective - Abd Kadir Ahmad (Punggawa Law Review, 2026)
This article examines Article 25 of Makassaarsche Chrestomathie, particularly the provision commonly associated with the abduction or taking of a woman within the normative setting of Makassarese customary law. The article treats the provision as a crucial point of entry into the older legal imagination of crime, marriage, kinship, and social order. The central difficulty lies in the fact that the offence cannot be read directly through the categories of modern penal law. What appears today as kidnapping, coercion, or forced marriage may have been articulated within a customary legal structure concerned with family authority, compensation, shame, status, and the restoration of disturbed communal relations. Using normative legal method, this article compares the Makassarese provision with global debates on bride kidnapping in Kyrgyzstan and ukuthwala in South Africa. The comparison does not assume equivalence between those legal cultures. Rather, it uses them to test how customary justification, consent, gendered authority, and state criminal law interact when marriage-related abduction is claimed as tradition. The article argues that Article 25 should be read neither as an archaic curiosity nor as an unproblematic form of indigenous justice. It contains a legal grammar that may preserve communal order, yet it also raises a hard question about whether the woman’s will is treated as legally decisive. In contemporary Indonesian criminal law, especially after the recognition of living law in Law No. 1 of 2023, this issue becomes more than historical.